Thermally-driven scintillator flow in the SNO+ neutrino detector - Wilson, JD (Elsevier, 2023)
The SNO+ neutrino detector is an acrylic sphere (radius 6 m) with a thin vertical neck containing almost 800 tonnes of liquid scintillator. The apparatus is immersed in a water-filled underground cavern, the neck protruding upward into a manifold above water level, with scintillator filling the sphere and rising up the neck some 6 m to an interface with purified nitrogen gas. Time-dependent flow simulations have been performed to investigate convective motion of the scintillator fluid, motivated by observations of a transient radon (222Rn) contamination layer which, over a period of two weeks, sank from near the base of the neck to the detector’s equator. According to simulations, this motion may have been induced by heat transfer through the detector wall, that resulted in buoyant ascending flow within a thin wall boundary layer and compensating sink elsewhere. This mechanism can result in transport down the neck to the sphere on a time scale of several hours. If the scintillator happens to be thermally stratified, the same forcing by a weak wall heat flux produces internal gravity waves in the spherical flow domain, at the Brunt–Väisälä frequency. Nevertheless as oscillatory motion is by its nature non-diffusive, simulations confirm that imposing strong thermal stratification over the depth of the neck can mitigate mixing due to transient heat fluxes.